Fixation and Stabilization of Heavy Metals in a Product Composed of Fly Ash and Industrial Acidic Wastes - Polat, Mehmet; Üzelyalçın Ülkü, Berna (Izmir Institute of Technology, 2010)
Large quantities of fly ash are produced in the world while only a very small portion of it finds utilization as a product. Since even larger quantities of fly ash should be expected to be generated in an increasingly energy-hungry world, finding new, smart pathways towards fly ash utilization carries its own weight in achieving sustainable development. Manufacturing light-weight fly ash aggregates which could also be used as sinks for other wastes with acceptable environmental foot-print and possible added value is exactly one such pathway. This thesis comprises of the studies where a fly ash sample from a large Thermal Power Plant (Soma fly ash) is used to stabilize an extremely acidic industrial waste in an aggregate structure with the aim that the aggregates produced had acceptable environmental impact and possible product value. The study is divided into several parts. Initial chapters contain the characterization studies of both the fly ash from Soma, Manisa Thermal Power Plant and the highly acidic industrial waste from a metal stripping factory in Cigli-Izmir. Later chapters contain the methodology and the experimental parts of the work. The acidity of the aggregates was also optimized keeping in mind the present environmental regulations. Solid/liquid ratio, effect of aging of the aggregates, effect of leaching from the aggregates and their mechanical strengths were the main experimental parameters investigated. Mineralogical composition of the aggregates was compared with the raw fly ash to shed light on the fixation mechanism. The fly ash was rich in especially Si, Al and Ca and some heavy metals in trace amounts whereas the acidic waste contained huge amounts of Zn, Fe and other heavy metals. This study demonstrated conclusively that the acidic waste was not only neutralized by the fly ash to disposable levels, but also that the leaching of both the major and minor elements from the aggregate body into the water was below the environmental limits in force both in Europe and Turkey today. The produced aggregates were also observed to possess the low-strength-material properties which open the possibility for their utilization in construction applications.
Thesis (Doctoral)--Izmir Institute of Technology, Chemical Engineering, Izmir, 2010
Includes bibliographical references (leaves: 137-149)
Text in English; Abstract: Turkish and English
xvii, 149 leaves
Keywords: Heavy metals--Environmental aspects; Fly ash analysis